EFFECT OF POVIDONE IODINE TREATMENT ON BACTERIAL COMMUNITY ASSOCIATED WITH WHITE SHRIMP (LITOPENAEUS VANNAMEI) LARVAE - Pangastuti, Artini; Suwanto, Antonius; Lestari, Yulin; Suhartono, Maggy T. (Marine Research in Indonesia, 2009)
The efficacy of povidone iodine as a surface disinfectant was assessed in white shrimp (Litopenaeus vannamei) eggs and larvae. Eggs and nauplii were exposed to povidone iodine 20 ppm for 20 seconds. Culture-based method and Terminal Restriction Fragment Length Polymorphism (T-RFLP) were used to monitor the total number of bacteria and diversity of the bacterial community associated with shrimp eggs and larva at each developmental stage. Povidone iodine reduced the total culturable bacteria, especially Vibrio, on eggs and nauplii, as well as the total bacteria in the whole community as estimated by T-RFLP results. Povidone iodine also reduced the diversity of bacterial community and altered the evenness of phylotypes distribution suggesting that the use of povidone iodine as a surface disinfectant in shrimp aquaculture should be reconsidered.